O02.6 Extragenital mycoplasma genitalium infections amongst men who have sex with men. (14th July 2019) - Latimer, Rosie; Vodstrcil, Lenka; Read, Tim; Petra, Vesna De; Fairley, Christopher; Williamson, Deborah; Chow, Eric; Bradshaw, Catriona
Abstract : Background: There are limited data on the prevalence of Mycoplasma genitalium (MG) coinfection with rectal chlamydia and rectal gonorrhoea infections in men who have sex with men (MSM). There are also few studies examining the prevalence of pharyngeal MG in MSM. Using a highly sensitive transcription mediated amplification assay, this study aimed to determine the proportion of rectal chlamydial and gonococcal infections in MSM that are co-infected with rectal MG, and the proportion of MSM with MG detected in the pharynx. Methods: This study was conducted at Melbourne Sexual Health Centre in Victoria, Australia. Consecutive routinely collected rectal swabs from MSM, that previously tested positive for chlamydia (N=212) or gonorrhoea (N=212) using Aptima Combo 2 (Hologic, San Diego), were tested for MG co-infection using the Aptima Mycoplasma genitalium Assay (Hologic, San Diego). Consecutive pharyngeal samples (N=500) from MSM were also tested for MG using Aptima Mycoplasma genitalium Assay. Samples were linked to demographic and epidemiological data, as well as symptoms and clinical diagnosis, and irreversibly de-identified prior to MG testing. Results: Rectal-MG was co-detected in 27/212 chlamydial (13%, 95%CI 9–18) and in 29/212 gonorrhoea (14%, 95%CI 9–19) samples, with no difference in the proportion positive for MG between the two groups (p=0.774). MSM with rectal-gonorrhoea and MG co-infection were more likely to be HIV positive than those infected with gonorrhoea alone (OR 2.96, 95%CI 1.21–7.26, p=0.023). Pharyngeal-MG was detected in 8/464 consecutive samples (2%, 95%CI 1–3%). Conclusion: We found high and identical rates of MG coinfection (13–14%) in MSM with chlamydial or gonorrhoeal rectal infection. Macrolide resistance in MG exceeds 80% in MSM at our service. Rectal gonorrhoea and chlamydia treatment involves use of azithromycin. These data highlight the prevalence of unidentified MG which is inadvertently exposed azithromycin. Using highly sensitive diagnostic methods, pharyngeal-MG was only detected in 2% of MSM in this study. Disclosure: No significant relationships.